Exploring available water resources in Bahraich district of Uttar Pradesh: A comprehensive study - CHAUDHARI, SHIV SHANKER; SUDHISHRI, SUSAMA; DASS, ANCHAL; KHANNA, MANOJ; KUMAR, PRAMOD; SEHGHAL, VINAY KUMAR; PADARIA, RABINDRA; V A, BLESSY; KUMAR, LOVE (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during 2018–22 at Bahraich, Uttar Pradesh focusing on groundwater, runoff, and canal water suggesting that a sizable database is essential for effectively managing water resources. Groundwater quantity was estimated using water level fluctuation (WLF), runoff using GIS coupled with curve number and canal water volume using equivalent length factor methods. This study revealed that the contribution of groundwater was more than 52.5%, whereas runoff (45.61%) and canal water (1.89%). Higher amounts of total available water observed in Mihipurwa (305.3 million cubic meter, MCM), Mahsi (211.6 MCM), Chittaura (189.3 MCM) and Nawabganj (184.4 MCM) blocks due to denser vegetation cover and moderate to low curve number values, while Risia (96.5 MCM) had the lowest amounts of available water in juxtaposition with the other blocks due to high industrial draft, higher drop down in the depth of post-monsoon groundwater level and minimal canal water irrigation. The sandy soil predominant in Jarwal had the lowest annual runoff (117.54 mm) while Nawabganj had the highest (359.84 mm) followed by Balha and Huzoorpur due to having a higher elevation over the other blocks. The runoff ratio was found to be larger in Nawabganj (27.74%), followed by Balha (23.06%) and lowest in Mihipurwa (14.89%) followed by Chittaurah (14.91%). Kaisarganj (11.6 MCM) had the highest amount of canal water resources accessible, followed by Mahsi (6.8 MCM) and Huzoorpur (6.1 MCM), while Balha and Nawabganj had the lowest amounts of canal water resources at 0.1 MCM.